'25 degrees of separation' Versus the 'ease of doing it closer to home': Motivations to Offshore Surrogacy Arrangements Amongst Australian Citizens. (March 2015) - Riggs, Damien W.
<x xml:space="preserve">Abstract</x> At present, onshore commercial surrogacy is illegal in all Australian states and territories. By contrast, offshore commercial surrogacy is legal in all bar one territory and two states. As a result, significant numbers of Australian citizens undertake travel each year to enter into commercial surrogacy arrangements. The present paper reports on findings derived from interview data collected with 21 Australian citizens who had children through an offshore commercial surrogacy arrangement, either in India or the United States. Framed by an understanding of the vulnerability that arises from the demand of reproductive citizenship, the analysis focuses specifically on whether or not the participants would have entered into an onshore commercial surrogacy arrangement had this been legal at the time. The findings suggest that for some participants, undertaking surrogacy 'at a distance' was perceived to be safer and provided a degree of privacy, whilst for other participants surrogacy closer to home would have removed some of the more challenging aspects of offshore arrangements. With these findings in mind, the paper concludes by considering Jenni Millbank's (2014) suggestion that Australian states and territories should legalise onshore commercial surrogacy, and the barriers that may exist to the uptake of such potential legal change.